The origin and evolution of human ampliconic gene families and ampliconic structure - Bhowmick, Bejon Kumar; Satta, Yoko; Takahata, Naoyuki (Genome Research, 2007)
Out of the nine male-specific gene families in the human Y chromosome amplicons, we investigate the origin and evolution of seven families for which gametologous and orthologous sequences are available. Proto-X/Y gene pairs in the original mammalian sex chromosomes played major roles in origins and gave rise to five gene families: XKRY, VCY, HSFY, RBMY, and TSPY. The divergence times between gametologous X- and Y-linked copies in these families are well correlated with the former X-chromosomal locations. The CDY and DAZ families originated exceptionally by retroposition and transposition of autosomal copies, respectively, but CDY possesses an X-linked copy of enigmatic origin. We also investigate the evolutionary relatedness among Y-linked copies of a gene family in light of their ampliconic locations (palindromes, inverted repeats, and the TSPY array). Although any pair of copies located at the same arm positions within a palindrome is identical or nearly so by frequent gene conversion, copies located at different arm positions are distinctively different. Since these and other distinct copies in various gene families were amplified almost simultaneously in the stem lineage of Catarrhini, we take these simultaneous amplifications as evidence for the elaborate formation of Y ampliconic structure. Curiously, some copies in a gene family located at different palindromes exhibit high sequence similarity, and in most cases, such similarity greatly extends to repeat units that harbor these copies. It appears that such palindromic repeat units have evolved by and large en bloc, but they have undergone frequent exchanges between palindromes.